Analyses of glass tesserae from Kilise Tepe: New insights into an early Byzantine production technology. (February 2017) - Neri, Elisabetta; Jackson, Mark; O'Hea, Margaret; Gregory, Tom; Blet-Lemarquand, Maryse; Schibille, Nadine
Abstract: There is substantial archaeological evidence to suggest that glass mosaics were ubiquitous throughout late antique and Byzantine Asia Minor. However, issues about the manufacture of Byzantine glass tesserae, the diffusion of their technology and the economic implications have been little discussed. This paper presents the results of the analytical and technological investigation of 28 glass fragments from Kilise Tepe (Cilicia, Turkey), including 22 tesserae, 3 gilded plaques and 1 fragment of a window, a vessel and an ingot. The samples were analysed by EPMA, LA-ICP-MS and SEM-EDS. Two different base glasses from different primary production sites were used in the production of the glass: Foy-2 probably from Egypt, and Levantine I produced in Syro-Palestine. Variations in the chemical fingerprint and morphology of crystalline particles reveal differences in the colouring and opacifying techniques that may point to multiple secondary production sites. Whereas the red samples show signs of in situ crystallization of metallic copper, ready-made lead stannate was added as yellow pigment for the colouring of the green and yellow tesserae. In addition, calcium phosphate particles, likely deriving from bone-ash, were found in one turquoise specimen. When compared with other late antique sites, our results testify to changes in the Roman centralized production tradition and a diversification of supply and secondary manufacturing practices of mosaic tesserae. Highlights: Diversification of secondary production techniques in the production of tesserae was found. Colour specialisation in the production of mosaic tesserae is proposed. Different base glasses were used for the production of tesserae partially dependent on colour. Morphologies of crystalline particles reveal a great variety in the colouring and opacifying techniques.